Revolutionizing Sentiment Prediction: A Cutting-Edge Deep Learning Approach (International Journal of Food and Nutritional Sciences, 2022)
In light of its interactive and real-time nature, the exploration of public sentiment through theanalysis of extensive social data has gained significant attention. Recent studies leveragesentiment analysis and social media to track major events by monitoring user behavior.